Critical discourse analysis of Donald Trump’s tweets: An authentic teaching material for critical reading - Rahma Fitriana (Universitas Negeri Yogyakarta, 2023)
EFL learners need to develop their critical literacy when they are dealing with texts. By looking at the texts critically, students did not only comprehend the content of the text but also could train their language sensitivity, which examines whether the use of language is appropriate for the intended purposes, and could enhance their higher-order thinking capacity. Learners can practice their critical thinking by immersing themselves with Critical Discourse Analysis (CDA) activities, which enable the learners to examine linguistic units, social contexts, and the writer’s ideology behind the texts. The study attempts to analyze the ideology and framing strategy in a series of tweets posted by the former President of the United States of America, Donald Trump (@realDonalTrump) on the issue of immigrants, national security, and travel ban. It employed a textual analysis using Huckin’s framework (1989) model of CDA and collected the tweets from @realDonaldTrump account, which talked about, or had direct relations with, those three interrelated issues. The findings showed that most of his tweets framed certain groups of people badly using provocative words, images, and videos. A critical reading task is possible to do by adopting critical analysis of these Twitter posts, where EFL readers are trained to be aware of the linguistic and multimodal elements in the tweets and make a link of those elements with textual features and the broader social contexts.